NMS medicine - Wolfsthal, Susan D. (National medical series for independent study, 2012)
"Through this comprehensive review of internal medicine, we sought to capture the essential concepts and key elements of our specialty by focusing on general internal medicine and the numerous medical subspecialties. Although internal medicine is constantly evolving, there are basic principles and thought processes that remain the essence of our specialty. Learning the facts is only the beginning. Medical students must develop their skills in deductive reasoning and synthesize these facts, weighing the pros and cons of the evaluation and management choices for their patients"--Provided by publisher.